TINDAK PIDANA NARKOTIKA OLEH RESIDIVIS: ANALISIS PENJATUHAN PIDANA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Yulianis Safrinadiya Rahman; Sri Herlina (Al-Adl : Jurnal Hukum, 2026)
One of the significant challenges in criminal law is the prevalence of narcotics offenses committed by recidivists—individuals who reoffend after having previously served a sentence. Recidivist status creates complex juridical dilemmas, as it serves as a statutory ground for sentence aggravation, often resulting in severe verdicts ranging from life imprisonment to the death penalty. This practice triggers a debate regarding the fundamental objectives of sentencing, where judges are compelled to strike a balance between retribution (retributive justice) to ensure deterrence, prevention (preventative justice), and rehabilitation (rehabilitative justice) aimed at social reintegration. This study aims to examine the legal framework governing narcotics offenses under Law Number 35 of 2009 concerning Narcotics and the specific sentencing mechanisms applied to repeat offenders. This research employs a normative legal methodology, utilizing secondary data through library research to analyze relevant statutes and legal literature. The findings demonstrate that the sentencing system under the Narcotics Law mandates aggravated penalties for offenders involved in organized networks, those involving minors, and those with recidivist status. Sentencing for narcotics recidivists emphasizes enhanced sanctions; while Articles 486 to 488 of the Criminal Code (KUHP) establish general provisions for recidivism, Article 144 of Law Number 35 of 2009 specifically stipulates that recidivists may be subject to an additional one-third of the maximum prescribed penalty.